Cash on demand - Chantler, David T. 1925-2012; Cushing, Peter 1913-1994; Morell, André 1909-1978 (Powerhouse Films, 2021)
"It's Christmas week, and in the office of City & Colonial Bank in Haversham, it's a quiet day. The small staff is managed by Harry Fordyce (Peter Cushing), a business-only nerd who exudes no warmth, no holiday spirit, and does not fraternize with the help. He won't even let the staff put up Christmas decorations. Today there is a ten pound discrepancy and he's making a big hullabaloo about it, even though the error was spotted. In walks Colonel Gore Hepburn (Andre Morrell), who represents the bank insurance company. He is doing a surprise inspection of the security. When he's alone with Fordyce, he informs him that he's a thief, there to steal the bank's money, and that he's holding Fordyce's wife and child hostage. One signal from the window, and they're done with. Hepburn has the robbery planned down to the second, and Fordyce must play along. In the outer office, Hepburn acts like an efficient man, checking out the floor signals. Fordyce is a wreck but tries not to show it. He carries out all of his instructions, which include putting the money into suitcases (Hepburn's "luggage"). Very suspenseful film, and one wonders if Hepburn will be able to get away with the robbery, and if Fordyce will be implicated in any way."
Bildformat 1.66:1
Special features: High definition remaster ; Original mono audio ; Two presentations of the film: the original UK theatrical cut (67 mins) and the extended US version (81 mins) ; Audio commentary with film historians Jonathan Rigby and David Miller ; The Perfect Crime: Inside 'Cash on demand' (2018, 19 mins): an analysis of the film and its production by Hammer expert Jonathan Rigby, BFI curator Josephine Botting and cultural historian John J Johnston ; Hammer's Women: Lois Daine (2018, 10 mins): critic and author Becky Booth on the popular English actress ; Lois Daine on 'Cash on demand' (2018, 8 mins): new and exclusive interview ; Original theatrical trailer ; Image galleries: press and promotional material ; New and improved English subtitles for the deaf and hard-of-hearing
Original © 1961, renewed 1989 Columbia Pictures
Keywords: Film; Blu-Ray-Disc